Arterial retention of apolipoprotein B48- and B100- containing lipoproteins in atherogenesis - Proctor, Spencer; Vine, Donna; Mamo, John (Lippincott Williams & Wilkins, 2002)
Purpose of review: The ‘response to retention’ hypothesis of atherosclerosis suggests that the arterial deposition of cholesterol is directly proportional to the concentration of circulating plasma lipoproteins. However, there is increasing evidence to support the concept that specific lipoproteins may be preferentially retained within the arterial wall, possibly as a result of greater affinity for cell surface and extracellular matrices. Recent findings: Recently, key studies have provided insight into mechanisms involved in the interaction of apolipoprotein B (apoB)-containing lipoproteins with extracellular matrices. In addition, novel methods and innovative experimental design has enabled us to differentiate between the delivery, retention and efflux of apoB48- and apoB100-containing lipoproteins. Other studies have demonstrated a relationship between extracellular matrix proteoglycan expression and the development of atherosclerosis in vivo. Discussion in the present review also extends to the mechanisms that are involved in the relative intimal retention of apoB48- and apoB100-containing lipoproteins in order to explain the atherogenicity of these macromolecules. Summary: The perspective of this review is to highlight recent advances in the area of arterial lipoprotein retention and the physiological significance these processes may have in the aetiology of cardiovascular disease. Importantly, an understanding of the mechanisms responsible for the retention of apoB48/B100-containing lipoproteins will enable new strategies to be developed for the future management of cardiovascular disease.